2020
DOI: 10.1111/all.14174
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with T cell–mediated cutaneous adverse drug reactions: A PRISMA‐compliant systematic review—An EAACI position paper

Abstract: Abderrahim Oussalah and Vincent Yip First authors share an equal contribution.Jean-Louis Guéant and Munir Pirmohamed Senior authors share an equal contribution. AbstractDrug hypersensitivity reactions (DHRs) are associated with high global morbidity and mortality. Cutaneous T cell-mediated reactions classically occur more than 6 hours after drug administration and include life-threatening conditions such as toxic epidermal necrolysis, Stevens-Johnson syndrome, and hypersensitivity syndrome. Over the last 20 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 158 publications
(706 reference statements)
0
14
0
1
Order By: Relevance
“…Single HLA associations up until 2019 have been extensively reviewed (White et al, 2015;Karnes et al, 2019;Oussalah et al, 2020). Since then, further advancement in sequencing platforms has been providing increased resolution that has enabled discovery of novel HLA associations (LaHaye et al, 2016;van der Ven et al, 2018;Giannopoulou et al, 2019;Mimori et al, 2019 (Zhao et al, 2020).…”
Section: Recently Reported Hla Associations (2019-)mentioning
confidence: 99%
“…Single HLA associations up until 2019 have been extensively reviewed (White et al, 2015;Karnes et al, 2019;Oussalah et al, 2020). Since then, further advancement in sequencing platforms has been providing increased resolution that has enabled discovery of novel HLA associations (LaHaye et al, 2016;van der Ven et al, 2018;Giannopoulou et al, 2019;Mimori et al, 2019 (Zhao et al, 2020).…”
Section: Recently Reported Hla Associations (2019-)mentioning
confidence: 99%
“…A recent EAACI position paper performed an exhaustive revision about advances on the role of genetic susceptibility in DHRs. Genetic variations in HLA associated with susceptibility to hypersensitivity reactions for some drugs highlight the need to confirm current knowledge and to identify new associations for more accurate diagnosis, treatment, and management 96 (Figure 3).…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…8,10 Despite a high prevalence of nonimmediate reactions to penicillins, little is known about the influence of genetic determinants, in contrast to the pharmacogenetic data published on immediate reactions. [11][12][13][14] An Italian case-control study by Romano et al 15 assessed the HLA-A2 and HLA-DRw52 alleles in 24 patients with MPE caused by delayed hypersensitivity to aminopenicillins compared to 522 subjects from the general population and found that they were significantly more prevalent among the former. However, it is noteworthy that no genome-wide association study (GWAS) or HLA genotyping with next-generation sequencing (NGS) has been performed to evaluate the contribution of the genetic determinants.…”
Section: Introductionmentioning
confidence: 99%